Long-term outcome and athletic level following operative treatment for osteochondritis dissecans of the knee in pediatric and adolescent patients - Bangert, Yannic; Zarembowicz, Patrick; Engelleiter, Karoly; Gkarilas, Evangelos; Schmitt, Holger; Renkawitz, Tobias; Jaber, Ayham (Journal of Clinical Medicine, 2023)
Research on the long-term outcomes following surgical therapy for osteochondritis dissecans (OCD) of the knee is scarce. A single-center retrospective cohort study was conducted to investigate surgically treated patients for knee OCD between 1993 and 2007. A total of 37 patients with an average follow-up duration of 14 years (range 8-18) were in the final cohort. IKDC and Lysholm scores were assessed. The duration and types of sport activity were reported. Long-term results were compared with existing midterm data. Knee scores showed a very good outcome with a mean of 91.3 in the IKDC score and 91.7 in the Lysholm score. Compared to midterm outcomes, both IKDC (p = 0.028) and Lysholm scores (p = 0.01) improved on final follow-up. Patients with open physes showed a significantly better Lysholm score compared to patients with closed physes (p = 0.034). Defect localization and size did not influence the outcome, but a defect depth of <0.8 cm2 achieved significantly better scores than ≥0.8 cm2. Of all surgical interventions, refixation achieved the best outcome. Long-term results significantly improved compared to midterm results with a follow-up of 40 months (p = 0.01). Thirty-six out of 37 patients were physically active, with 56% of sports being knee-straining activities. Long-term results following surgically treated OCD fragments show excellent function and a good athletic level. Patients with open physes potentially have better knee outcomes. Midterm results are sustainable and could improve further in the long term.